Effectiveness of oral rehydration in the management of dehydration in children with acute gastroenteritis: Case Review and Analysis - Siti Maulidiya; Darmi Arda; Darmiati Darmiati (Edukasi Ilmiah Indonesia, 2025)
Introduction: Acute gastroenteritis is a leading cause of dehydration in children and is commonly encountered in healthcare settings. It presents with symptoms such as diarrhea and vomiting, which lead to significant fluid and electrolyte loss. If not managed promptly, dehydration can result in serious complications, including death. Oral rehydration therapy (ORT) has long been recommended as a first-line, effective treatment for mild to moderate dehydration in pediatric patients. This study aimed to evaluate the effectiveness of oral rehydration solution (ORS) in treating dehydration caused by acute gastroenteritis in children. Methods: This descriptive case study involved two male pediatric patients, aged 1 and 2 years, who presented with dehydration due to gastroenteritis. The intervention included administration of ORS at a dosage of 40–100 ml/kg within the first 4–6 hours, accompanied by clinical monitoring over three days. Clinical parameters observed included frequency of defecation, skin turgor, oral mucosa condition, eye appearance, and level of consciousness. Results: Both patients showed improvement in clinical signs of dehydration. The frequency of defecation decreased from 4–5 times to 1–2 times per day. Skin turgor normalised, oral mucosa became moist, eyes appeared less sunken, and both children became more active and responsive. No adverse effects were reported, and both subjects responded positively to the therapy. Conclusion: Oral rehydration therapy using ORS effectively manages dehydration caused by acute gastroenteritis in children. It is a safe, simple, and accessible method that can be utilised in clinical settings and at home as a first-line response to dehydration